Not a little monkey - Zolotow, Charlotte, 1915-; Chessare, Michele ([New York] : Harper & Row, 1989)
A little girl tries to get her busy mother to play with her by doing a series of silly things, from pouring water on her head to climbing into the big wastebasket.
2.0
K-3
Keywords: Mothers and daughters -- Fiction; Mothers and daughters -- Fiction